Development of a phenotypic screening assay to measure activation of cancer-associated fibroblasts - Marcus M. Ilg; Alice R. Lapthorn; Sophie L. Harding; Tariq Minhas; Gouri Koduri; Stephen A. Bustin; Selim Cellek (Frontiers in Pharmacology)
BackgroundIn cancer metastasis, tumor cells condition distant tissues to create a supportive environment, or metastatic niche, by driving the activation of cancer-associated fibroblasts (CAFs). These CAFs remodel the extracellular matrix, creating a microenvironment that supports tumor growth and compromises immune cell function, enabling cancer cells to evade immune detection. Consequently, targeting the activation of CAFs has been proposed as a therapeutic strategy to hinder metastatic spread. Our objective was to develop the first in vitro phenotypic screening assay capable of assessing this activation process.MethodsHuman primary lung fibroblasts were co-cultured with highly invasive breast cancer cells (MDA-MB-231) to identify changes in the expression of selected genes using RT-qPCR. An In-Cell ELISA (ICE)-based assay using human lung fibroblasts, MDA-MB-231 cells and human monocytes (THP-1 cells) was developed to measure the activation of CAFs. Another ELISA assay was used to measure released osteopontin.ResultsWhen lung fibroblast were co-cultured with MDA-MB-231 cells, among the 10 selected genes, the genes for osteopontin (SPP1), insulin like growth factor 1 (IGF1), periostin (POSTN) and α-smooth muscle actin (α-SMA, ACTA2) elicited the greatest fold change (55-, 37-, 8- and 5-fold respectively). Since osteopontin, IGF-1 and periostin are secreted proteins and α-SMA is an intracellular cytoskeleton protein, α-SMA was chosen to be the readout biomarker for the ICE assay. When fibroblasts were co-cultured with MDA-MB-231 cells and monocytes in the 96 well ICE assay, α-SMA expression was increased 2.3-fold yielding a robust Z′ of 0.56. A secondary, low throughput assay was developed by measuring the release of osteopontin which showed a 6-fold increase when fibroblasts were co-cultured with MDA-MB-231 cells and monocytes.DiscussionThis phenotypic assay is the first to measure the activation of CAFs in a 96-well format, making it suitable for medium-to high-throughput screening of potential therapeutic compounds. By focusing on observable cellular phenotypic changes rather than targeting specific molecular pathways, this assay allows for a broader and unbiased identification of compounds capable of modulating CAF activation.